Reliability of a 60-min treadmill running protocol in the heat: The journal Temperature toolbox - Mündel T; Gilmour S; Kruger M; Thomson J (Taylor and Francis Group, 2022)
We determined the reliability of a 60-min treadmill protocol in the heat when spaced >4 weeks apart, longer than the test–retest duration of 1 week found in the literature. Nine unacclimated, trained males (age: 31 ± 8 y; VO2peak: 60 ± 6 ml∙kg−1∙min−1) undertook a 15 min self-paced time-trial pre-loaded with 45 min of running at 70% of individual ventilatory threshold (11.2 ± 0.3 km∙h−1) in 30 ± 1°C (53 ± 5% relative humidity). They repeated this following 40 ± 14 and 76 ± 26 days, with pre-trial standardization of diet and exercise for 48 h. When considering trial 1 as a familiarization, change in core temperature (∆Tcore) during the first 45 min (∆2.0 ± 0.2°C) between trials 2 and 3 yielded bias and 95% limits of agreement (LoA) of −0.10 ± 0.43°C, standard error of measurement (SEM) of 0.13°C and intraclass correlation coefficient (ICC) of 0.75, more reliable than measures of baseline Tcore (36.9 ± 0.2°C; LoA: −0.23 ± 0.90°C; SEM: 0.22°C; ICC: 0.03) and Tcore at 45 min during exercise (38.9 ± 0.4°C; LoA: 0.32 ± 1.12°C; SEM: 0.28°C; ICC: 0.15). The coefficient of variation (CV) between trials 2 and 3 for distance run during the 15 min time-trial was 2.1 ± 2.0% with LoA of 0.001 ± 0.253 km and SEM of 0.037 km. This protocol is reliable spaced ~5 weeks apart when considering the most commonly accepted limit of <5% CV for performance, reinforced by reliability of the ΔTcore being 0.1 ± 0.4°C.
© 2022 The Author(s)
Keywords: Exercise; heat; performance; core temperature; reliability